Healthcare Costs, School Performance, and Health-related Quality of Life in Adolescence Following Psychotic Experiences in Preadolescence: A Longitudinal Cohort Study. (21st December 2020) - Rimvall, Martin Køster; Wolf, Rasmus Trap; Olsen, Else Marie; Skovgaard, Anne Mette; Clemmensen, Lars; Oxholm, Anne Sophie; Verhulst, Frank; Rask, Charlotte Ulrikka; van Os, Jim; Jeppesen, Pia
Abstract: Psychotic experiences (PEs) are common in the general population in preadolescence. The implications of PEs on socioeconomic outcomes, including educational attainment, are scarcely described. We aimed to estimate how preadolescent PEs were associated with later healthcare costs, school performance, and health-related quality of life (HRQoL) in adolescence. A total of 1607 preadolescents from the general population Copenhagen Child Cohort 2000 were assessed for PEs at age 11–12 years and followed up over 5 years using register-based data on mental and somatic healthcare costs, and school performance at age 16. Furthermore, HRQoL was assessed for a subsample of the children at age 16–17. We adjusted for perinatal and family sociodemographic adversities, prior parental mental illness and healthcare use, child IQ-estimate at age 11–12, and parent-rated general psychopathology of their child. PEs were associated with slightly poorer school performance. However, preadolescents with PEs more often reported HRQoL within the lowest 10th percentile (OR = 2.74 [95% CI 1.71–4.37]). Preadolescents who reported PEs had higher average total healthcare costs over the following 5 years. The costs for individuals with PEs were higher for mental healthcare services across primary to tertiary care, but not for somatic care. After adjustments, PEs remained independently associated with higher costs and poorer HRQoL, but not with poorer school performance. In conclusion, PEs are important in mental health screening of preadolescents and identify a group of young people with increased healthcare service-use throughout adolescence and who report poorer HRQoL in adolescence, over and above parent-rated general psychopathology of their child.